Critical Tests of Multiple Theories of Cultures' Consequences: Comparing the Usefulness of Models by Hofstede, Inglehart and Baker, Schwartz, Steenkamp, as well as GDP and Distance for Explaining Overseas Tourism Behaviour - Hsu, Shih-Yun; Woodside, Arch; Marshall, Roger (SAGE Publications Inc, 2013)
The study provides critical tests of the usefulness of four alternative theories, proposed by Hofstede, Inglehart, Schwartz, and Steenkamp, of national cultures’ influences for explaining consumers’ consumption of international services. The study applies critical testing of these four theories in two research contexts: visiting Australia by holiday (vacation) travelers from 5 Asian and 5 Western nations and visiting the United States by holiday (vacation) travelers from 12 nations. The study is unique and valuable in proposing and testing configurational perspectives of cultural influences rather than testing via “unpacking” the net effects of cultural dimensions separately. The findings indicate that cultural configurations do impact consumption behavior of international services beyond the influences of demographic conditions (distance and national wealth) and that Schwartz’s theory is useful in particular in explaining unique aspects of consuming international services.